2004
DOI: 10.1111/j.1365-246x.2004.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Indication of the uplift of the Ardenne in long-term gravity variations in Membach (Belgium)

Abstract: S U M M A R YWe report on the results of 7 yr of collocated gravity observations made with an FG5 absolute (AG) gravimeter and a GWR C-Series superconducting gravimeter (SG) located at the Membach Geophysical Station in eastern Belgium. The SG gravity residuals track changes in gravity periodically observed by the AG, at the microgal level. Further, in the SG residual signal we distinguish a quasi-seasonal term that can be mostly explained by variations in local water storage effects. In the AG time-series we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 28 publications
4
42
0
Order By: Relevance
“…Since the development of lGal (1 lGal = 10 -8 m s -2 ) precision absolute gravimetry (AG) (NIEBAUER et al, 1986), collocated AG and GPS campaigns have become more frequent for a wide range of applications (HINDERER et al, 2003;FRANCIS et al, 2004;MÜ LLER et al, 2005;AMALVICT et al, 2006). This also applies when continuously monitoring the time-variable gravity field with superconducting gravimeters and the geodetic positions with GPS, VLBI or SLR at fixed observatories (CROSSLEY et al, 1999;ZERBINI et al, 2001ZERBINI et al, , 2002IHDE et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Since the development of lGal (1 lGal = 10 -8 m s -2 ) precision absolute gravimetry (AG) (NIEBAUER et al, 1986), collocated AG and GPS campaigns have become more frequent for a wide range of applications (HINDERER et al, 2003;FRANCIS et al, 2004;MÜ LLER et al, 2005;AMALVICT et al, 2006). This also applies when continuously monitoring the time-variable gravity field with superconducting gravimeters and the geodetic positions with GPS, VLBI or SLR at fixed observatories (CROSSLEY et al, 1999;ZERBINI et al, 2001ZERBINI et al, , 2002IHDE et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists have modeled the effects of land-water distribution on the observed gravity (e.g., Francis et al, 2004;Abe et al, 2006;Boy and Hinderer, 2006;Meurers et al, 2007;Jahr et al, 2009;Leirião et al, 2009;Longuevergne et al, 2009;Nawa et al, 2009;Pfeffer et al, 2011). For example, Hanada et al (1990) found a simple proportional relationship between water level and abCopyright c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a Singular Spectrum Analysis (SSA) and found a period of 15 years for both the SG and AG time series shown on Figure 4. This oscillation has the potential to have biased the analysis of Francis et al [2004], who discussed a possible decrease in gravity of −6 ± 2 nm/s 2 /yr, based on data spanning 1996-2002. To investigate this possibility, we investigated the stability of our estimates of gravity rates of change as a function of the length of the AG time series, both using all the available data and limiting the series to 2 measurements per year (spring and fall), in order to be consistent with the profile.…”
Section: Long-term Climatic Effectsmentioning
confidence: 99%
“…This uncertainty increases to about 3 nm/s 2 /yr when limiting the series to 2 measurements per year; this is similar to the uncertainty obtained on the data from the profile. The epoch of the Francis et al [2004] study, which corresponded to the decreasing part of the 15 yr quasiperiodic signal, is indicated by a vertical line. The value published in 2004 (−6 nm/s 2 /yr) is slightly different from what can be seen on Figure 5a (∼−4.5 nm/s 2 /yr), as the annual term and the drift of the rubidium clock were not taken into account at that time.…”
Section: Long-term Climatic Effectsmentioning
confidence: 99%
See 1 more Smart Citation